It’s not difficulty that matters, but strategy: Perceived stressor, functional and dysfunctional coping strategies in ultra-trails of extreme duration - Pietro Trabucchi; Barbara Pellegrini; Aldo Savoldelli; Gianandrea Giacoma; Ilaria Vergine; Carlo Galimberti; Sara Garofalo; Federico Schena (PLoS ONE, 2025)
To date, no studies have proposed specific taxonomies of stressors and coping strategies used to manage them by ultra trail runners in races longer than 200 miles, with existing research focusing on significantly shorter distances an then on challenges that could be of a different nature. The aim of this study was to fill this gap by developing specific taxonomies that would group both the stressors encountered and the coping strategies into distinct conceptual categories. Furthermore, to observe in a real competition if these taxonomies allows the evaluation of the coping strategies used by athletes. Two Focus Groups composed of experts on the topic proposed provisional classifications, which were analysed using Applied Thematic Analysis. Three distinct Draft Taxonomies were identified: typical stressors, functional and dysfunctional coping strategies used by athletes during competitions. A critical comparison between the provisional taxonomies and literature led to the development of three definitive taxonomies. In a second phase, to verify whether the taxonomies reflected the real experiences of runners, seven participants in a 280-mile race were interviewed daily during the event. Their responses regarding the stressors and the strategies they had implemented to deal with them were recorded. Expert panelists categorized the transcribed responses according to the proposed taxonomies. The concordance of the judgments, verified with the Fleiss K, was considered a measure of the taxonomies’ ability to capture real experiences. Results confirmed substantial agreement between the raters regarding both the stressors (K = 0.711, p < 0.001) and the coping strategies (K = 0.73, p < 0.001). The analysis of the proportion between the use of functional and dysfunctional strategies proved to be high (between 0.66 and 1) among athletes who completed more than 50% of the race. The taxonomies were found to effectively described athletes’ race experiences, revealing context-specific coping strategies likely developed through years of practice.